Environmental scanning electron microscopy analysis of Proteus mirabilis biofilms grown on chitin and stainless steel - Fernández-Delgado, Milagro (Ann Microbiol, 2014)
Proteus mirabilis is a human pathogen able to form biofilms on the surface of urinary catheters. Little is known about P. mirabilis biofilms on natural or industrial surfaces and the potential consequences for these settings. The main aim of this work was to assess and compare the adhesion and biofilm formation of P. mirabilis strains from different origins on chitin and stainless steel surfaces within 4 to 96 h. Using environmental scanning electron microscopy, the biofilms of a clinical strain grown on chitin at 4 h showed greater adhesion, aggregation, thickness, and extracellular matrix production than those grown on stainless steel, whereas biofilms of an environmental strain had less aggregation on both surfaces. Biofilms of both P. mirabilis strains developed different structures on chitin, such as pillars, mushrooms, channels, and crystalline-like precipitates between 24 and 96 h, in contrast with flat-layer biofilms produced on stainless steel. Significant differences (p < 0.05) were found in the frequency of pillars and channels. Images of transmission electron microscopy demonstrated abundant fimbriae in 100 % of cells from both strains, which could be related to surface adherence and biofilm formation. This represents the first study of P. mirabilis showing adhesion, biofilm formation, and development of different structures on surfaces found outside the human host.